Ice and snow for winter sports - Maeno, N. (The engineering approach to winter sports, 2016)
In the past winter sports were played only in cold areas during winter, but the development of techniques to artificially produce snow and ice has changed the situation. Now winter sports are enjoyed even in summer and almost all over the world regardless of season and area. Ice and snow are indispensable to winter sports because they cover a variety of ground surfaces, mountains, forests, lakes and so on, and provide us surfaces on which we can walk and play. Moreover ice and snow prepare slippery surfaces necessary for various kinds of winter sports such as ski, skate, sledge, curling, etc. The slipperiness is the most important property of ice and snow for winter sports. It may be stupid to make a question why ice and snow are so slippery, but this inquiry gives an important key to understand the essential property of ice and snow. In physical sense slipperiness is not an intrinsic property of ice and snow. The homologous temperature is defined as T/Tm where T is the temperature and Tm is the melting point expressed in the absolute temperature (K). The homologous temperature 100% means the highest temperature any solid material can attain because it melts away at Tm; it is 1809 K (1536 °C) for iron and 273 K (0 °C) for ice. For instance, the homologous temperature 80 % is -55 °C for ice and 1174 °C for iron. —55 °C is quite a cold temperature for human beings, but it is extremely high temperature for ice and corresponds to iron heated to 1174 °C. We should remember that ice and snow we see are just like iron heated to red-hot and white-hot above 1000 °C.